Internet of Things based Control and Monitoring System for Koi Fish Cultivation - Kevin William; Ikhwan Ruslianto; Irma Nirmala (CESS (Journal of Computer Engineering, System and Science), 2023)
Water quality is an important factor for fish koi cultivation. Poor water quality such as inappropriate temperature, pH, and turbidity can disrupt metabolic processes, inhibit growth and cause death in koi fish. Apart from that, feeding and checking water quality are still done manually. Because of this, we need a system that can monitor and control the feeding, temperature, and water quality according to the living environment of koi fish. In this study the system was built on an Android-based mobile application using the flutter framework. In addition, the system has a notification to provide information on changes in sensor readings in real time to users. The notifications are changes in temperature, pH, turbidity, water level, feed level and changes in control device modes. Testing the water temperature readings obtained a relative error value of 0,66%, water turbidity readings obtained an error value of 8,79%, water pH readings obtained a relative error value of 2,45%, water level readings obtained an error relative value of 1,57% and feed availability readings obtained an error value of 3,1%.